Endocrine and metabolic complications in a national cohort of Slovene children and adolescents with Duchenne muscular dystrophy: real-world criteria for transition to vamorolone therapy - Jazbinšek, Sončka; Vrščaj, Eva; Šuput Omladič, Jasna; Butenko, Tita; Loboda, Tanja; Kotnik, Primož; Osredkar, Damjan (Frontiers in Endocrinology, 2025)
AimsTo assess the prevalence of endocrine/metabolic disorders among pediatric Duchenne muscular dystrophy (DMD) patients and identify individuals who would benefit from the new corticosteroid treatment available, vamorolone.MethodsA national pediatric cohort of DMD patients followed at University Children’s Hospital, University Medical Center Ljubljana in June 2025 was included in the study. The presence of endocrine/metabolic disorders was determined by clinical examination, laboratory data, and imaging at the last annual multidisciplinary evaluation.ResultsA total of 21 patients (average age 11.1, range 4.6-16.7 yrs) were included in the study. Two patients were corticosteroid-naive, the rest treated with deflazacort (average treatment duration 5.4, range 1.1-11.3 yrs). At the time of final follow-up, 90% were diagnosed with an endocrine and/or metabolic disorder. Short stature was present in 67% of patients, a decline in height standard deviation score (SDS) since the initiation of corticosteroid therapy was observed, -2.37 SDS on average. Based on body composition data (fat % SDS), 57% were classified as obese. Lipid abnormalities were detected in 76% of patients. Insulin resistance (determined by HOMA-IR) was increased in 9.5% of patients; type 2 diabetes was not detected.ConclusionOur findings demonstrate a high prevalence of endocrine and metabolic disturbances among patients with DMD. In light of emerging evidence on the potential benefits of vamorolone - particularly regarding bone health and growth - we identified a subgroup of patients most likely to benefit from its use. We propose that ambulatory, non-corticosteroid naive patients with pathological fractures, markedly reduced bone density, short stature, or significant growth deceleration could be considered for the therapeutic transition. Accordingly, we established national clinical criteria to guide individualized therapeutic transitions, aimed at optimizing clinical outcomes and ensuring efficient allocation of healthcare resources.